ADOLESCENTS AND EARLY ADULTS WITH ACNE VULGARIS: A SCOPING REVIEW ON PSYCHOLOGICAL AND PSYCHOSOCIAL IMPACTS AND QUALITY OF LIFE - Wianti, Arni; Heni, Heni; Setyowati, Rahayu; Nuraeni, Rina; Setyawati, Anita (Journal of Maternity Care and Reproductive Health, 2023)
Introduction: Acne vulgaris (acne) is one of the main reasons adolescents and early adults visit dermatology clinics. Several studies have found serious non-physiological effects of acne on adolescents and early adults. Objective: This scoping review aims to provide a comprehensive overview of the existing literature on the impact of acne on psychological, psychosocial, and quality of life aspects among adolescents and early adults. Methods: The scoping review was enforced based on Arskey and O'Malley's framework. A structured article search was performed on three databases, namely CINAHL Plus with Full-Text, Scopus, and ScienceDirect. Search words were determined based on elements of population, concept, and context. Article selection and reporting were enforced following the PRISMA-ScR pathway and based on inclusion and exclusion criteria. Results: This study analyzed thirteen articles (ten primary research articles and three literature study articles) which revealed that adolescents and early adults with acne could experience psychological and psychosocial problems as well as decreased quality of life. Discussion: The emergence of psychological and psychosocial impacts of acne was related to one another and could be a predictor of a decrease in the quality of life among adolescents and early adults with acne. Health professionals need to understand the needs of adolescents and early adults regarding the physiological and psychological management of acne